Delta-Sigma data converters theory, design, and simulation - Norsworthy, Steven R.; Schreier, Richard; Temes, Gabor C. (IEEE Press, 1996)
This comprehensive guide offers a detailed treatment of the analysis, design, simulation and testing of the full range of today's leading delta-sigma data converters. Written by professionals experienced in all practical aspects of delta-sigma modulator design, Delta-Sigma Data Converters provides comprehensive coverage of low and high-order single-bit, bandpass, continuous-time, multi-stage modulators as well as advanced topics, including idle-channel tones, stability, decimation and interpolation filter design, and simulation.